Expendable Bodies: Examining the Connection Between Ecoracism and Embodied Toxicity to Advance Eco-Social Justice Activism - Shinall, Vivian (Consilience, 2021)
Although current literature in the environmental humanities establishes the existence of ecoracism and embodied toxicity, the discourse does not explicitly identify the connection between these two phenomena. This research paper argues that ecoracism, as seen in instances such as the violation of indigenous rights experienced by the Standing Rock Sioux Tribe or the infringement of corporations on the sacred land of Maunakea, creates expendable bodies that are either invisible or negligible to the public. In this system, the suffering of the oppressed groups similarly goes unseen. This process can be specifically traced to instances of embodied toxicity, in which the contamination of communal land, water, or air with toxic waste is ignored by lawmakers. This research proposes a new framework for discussing toxic pollution by linking the creation of expendable bodies under ecoracism to the normalization of embodied toxicity. Further, upon examining contributions from prominent scholars of eco-social justice activism, this work illustrates the ways in which this new lens can be applied in order to advocate for those who suffer from embodied toxicity.